The implementation of ozone cleaning on two-step texturization of p-type silicon wafer - Md Daud, Mohd Norizam; Aadenan, Amin; Chin Haw, Lim; Mohd Nor, Najah Syahirah; Ibrahim, Mohd Adib; Mat Teridi, Mohd Asri (International Journal of Renewable Energy Development, 2025)
This study investigates the ozone treatment process that can be utilized across various fabrication stages to enhance the performance of silicon solar cells. The effectiveness of this treatment on p-type silicon surfaces was examined through the application of ozone dissolved in deionized water (DIO3) and the ultraviolet-ozone (UVO3) cleaning process prior to the two-step texturization procedure. The two-step texturization procedure applied in this work eliminates the use of silicon nitride (SiN) as an anti-reflective coating (ARC) layer for the elimination of toxic gases and leads to the environment-friendly fabrication of solar cells. An alternative to RCA, DIO3 and UVO3 represent promising chemical options for cleaning applications to eliminate the use of hazardous chemicals. It was discovered that the surface with the DIO3 treatment for 10 minutes resulted in a significantly enhanced surface quality on the p-type silicon wafer. In the DIO₃ cleaning, ozone is dissolved in deionized water  to create a highly oxidative solution capable of removing organic contaminants and particles effectively. In contrast, the UVO₃ treatment harnesses ultraviolet light to synthesize ozone directly on the wafer's surface, promoting the degradation of organic residues into volatile compounds, including CO₂ and H₂O. According to field emission scanning electron microscope (FESEM) micrographs and UV-visible spectrometer (UV-Vis) measurements, the textured wafer with DIO3 treatment improves the surface morphology and decreases the front surface reflection. As a result, the 10 minutes DIO3 treatments were reported optimal; the range size and height of the pyramid formed were 1.9–2.0 µm and 0.8–1.5 µm, offering a lower reflectivity value of below 12%, respectively. Results from the Atomic Force Microscope  (AFM) also confirm that the increase in average surface roughness from 203.65 nm to 300.27 nm was expected to improve light absorption. Moreover, this methodology leads to a considerable reduction in surface damage and is applicable to the silicon texturization process utilized in solar cell manufacturing.